Analisis Strategi Industrialisasi Pada Industri Mebel di Kelurahan Bukir, Kecamatan Gadingrejo, Kota Pasuruan, Jawa Timur - Fitri Luthfia Wachadah; Muhammad Alfin Syaiful Izza; Muhammad Yasin (Trending: Jurnal Manajemen dan Ekonomi, 2023)
The industrial sector is one of the main sectors as a driver of the national economy, in which the industrial sector is one of the main sectors of economic development, but still has to pay attention to conditions in other sectors. One of them is the furniture industry, the Bukir Pasuruan furniture industry which is able to bear the title of the main furniture producer in East Java. The Bukir furniture industry is able to make a significant contribution to improving the regional economy. Its existence has opened many jobs for the local community. The purpose of this study is to identify the potential in the carved furniture industry along with the strategies used to increase industrial activity. The method used in this research is in the form of descriptive statistics, namely research that describes the characteristics and actual conditions of an object of research with a strategy to increase industrial development by conducting a SWOT analysis. The results obtained from this study are that the potential in the carving furniture industry will continue if factors such as government support, skilled workers, adequate capital market share and good marketing strategies are continuously developed. From the SWOT analysis, a SWOT matrix is ​​also produced which can be used by craftsmen and entrepreneurs in developing their business strategy